Ecosystem services of recreational parks in downtown Łódź (Central Poland) - Długoński, Andrzej (Ecological Questions, 2018)
Ecosystem services (ES) are the benefits that society and economy derive from the environment through natural processes of ecosystems. Urban ecosystems contribute to public health and improve the quality of life of urban residents and should be taken into account when making decisions on sustainable urban development and revitalization. Recreational parks are very important components of green urban infrastructure. The aim of the study was to define the types and subtypes of ecosystem services in nine recreational parks located in the downtown zone of Łódź, Poland, using my own classification scheme (a case study). The research shows the diversification of ES depending on the park, and suggests that the potential of parks is currently not fully used. The planned revitalization of downtown Łódź could extend the range of ecosystem services.